Analysis Legal Impact of Cancellation Marriage in Religious Court - Aris, Nurwana; Busthami, Dachran; Auliyah Asra, Andi Nur (Faculty of Law, Universitas Muslim Indonesia, 2025)
Study This aiming For knowing marital status second according to legislation in Indonesia and For know impact law cancellation marriage in religious courts . Research This use method study normative law , namely studies verdict . Research Results show that : first , according to positive law Polygamy allowed but very limited For protect rights women and children . Husband who wants polygamous must own legitimate reason , get​ permission from wife first , and submit application to religious court . Meanwhile , according to complications law Islam polygamy allowed with condition tight , especially dam matter applicable fair to wives and children . Second , the judge's considerations regarding impact law cancellation marriage in decision Number 586/ Rev.G /2022/ PA.Mks . Although marriage both of his parents canceled However decision the No applicable ebb to rights children and children still entitled get right inheritance towards his parents as well as if child born​ That women , then the father also has the right become guardian of his child's marriage .